Kecemasan Komunikasi Mahasiswa saat Bimbingan Skripsi - Tegar Aprilio Armanda (IKIP Budi Utomo Malang, 2020)
Tegar Aprilio Armanda, NPM: 1532010014. “Student Communication Anxiety During Thesis Guidance (Analysis of Communication Anxiety To Alumni of Students of the Communication Studies Program Merdeka Madiun University Class of 2015). Communication Studies Program, Merdeka Madiun University, Supervisor : Maria Madgalena W., S.Sos, M.Si, Supervisor 2: Zulin Nurchayati, S.Psi, M.Si. Year 2020. The purpose of this study was to determine the cause and effect of communication anxiety between students of the Merdeka Madiun University Class of 2015 with the supervisor when conducting thesis guidance, forms of communication anxiety itself that have been experienced by students of Communication Studies Merdeka Madiun University Class of 2015, anticipatory steps taken by the Communication Sciences Merdeka Madiun University Class of 2015 students, how important is the handling of communication anxiety, data related to communication anxiety among final year students. This research uses descriptive qualitative method. Research data obtained through observation techniques, literature studies, interviews, and documentation. The informants came from the 2015 Communication Merdeka Madiun University alumni students. The results of this study are modeling and skill acquisition factors causing the emergence of communication anxiety, the type of communication anxiety perceived by informants is generalized context communication apprehension and situational communication apprehension, the form of communication anxiety perceived by informants is state anxiety, the most anticipatory step recommended by informants is to better understand the thesis material before the guidance and remain calm during the guidance.Keyword: Anxiety, Communication anxiety, Students of the Communication Studies Program Merdeka Madiun University Class of 2015,Thesis Guidance.